Tragedy and its subjective configurations - Agacino, Rafael (Re-presentaciones: Periodismo, comunicación y sociedad, 2023)
Demokratía has its opacities, both classical and contemporary. Its own dynamic cradles a latent stásis that emerges when conflict cannot be contained. Tragedy happens. The word has become an insufficient weapon even if in the future it will be the primary material and source of memory. So it is with the Dionysias and the Leneas. There, tragedy as an aesthetic piece about faits accomplis and irreversibles, inspires identity, Greek memory. In this essay the center is placed on that tragic memory, on the ex post that follows the tragic moment, and under the license of a "controlled anachronism", transports its categories to the present. With them, some emblematic pieces of our tragedy are analyzed, the one that has haunted us since September 11, 1973. The subjective configurations that they sediment are interpreted and also hint at their criticism. That is the spirit of the text.
Keywords: Tragedy; Subjectivity; military coup